Test of Weak Form Efficiency in the Indian Stock Market - Sharma, Renuka; Chander, Ramesh (Indian Journal of Finance, 2010)
The capital market is a perfect place to arrange funds for private entrepreneurs. The investors will put in their funds for these enterprises only if the securities listed on the stock exchanges are not mispriced. The exclusion of the notion of under pricing and overpricing of the securities on the stock exchanges leads to the prevalence of efficiency of the stock market. The notion- Efficient Market Hypothesis advocates a market place where all the information is instantaneously incorporated into the share prices and no market participant is in a position to earn abnormal returns. There are many studies which identified that capital markets are not efficient although they should be. The present study has studied the performance of equity capital market of India for a period of more than ten years (1997-2007). In the last decade, the Bombay Stock Exchange has faced all phases of bear and bull markets and the behavior pattern of stock prices have been examined through parametric and non parametric tests. So this study has made efforts to examine whether the long term analysis of the market results in support of increased efficiency or not.